2020
DOI: 10.1186/s12885-019-6486-3
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib-induced osteitis mimicking bone metastasis in a stage IV ALK-rearranged NSCLC patient: a case report

Abstract: Background: Targeted therapies are a standard of care for first-line treatment of Anaplastic lymphoma kinase (ALK)rearranged non small cell lung cancer (NSCLC). Giving the rapid pace of drug discovery and development in this area, reporting of adverse effects of ALK inhibitors is crucial. Here, we report a case of osteitis induced by an ALK inhibitor mimicking bone metastasis, a previously undescribed side effect of crizotinib. Case presentation: A 31-year-old woman with stage IV ALK-rearranged NSCLC presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In its dosage as an antimicrobial agent, we observed that the CERI-treated group showed significantly lower WBC counts than the vehicle group, which could be due to its ability to suppress the release of neutrophils (Guisier et al 2020 ). However, we found no indiscriminate variation in RBC, PLT, or HGB (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In its dosage as an antimicrobial agent, we observed that the CERI-treated group showed significantly lower WBC counts than the vehicle group, which could be due to its ability to suppress the release of neutrophils (Guisier et al 2020 ). However, we found no indiscriminate variation in RBC, PLT, or HGB (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…11 Treatment with ALK inhibitors is usually well tolerated; however, there are common class adverse events such as nausea, vomiting, diarrhea, pneumonitis, and cardiac toxicity. 12 Some less common adverse events have been reported as well including rectal perforation, 13 cataract, macular edema or blindness, 14,15 osteitis, 16 ventricular fibrillation, 17,18 pulmonary arterial hypertension, 19 pancreatitis, 20 cholestasis, 21 alopecia, 22 proteinuria, 23 myasthenia gravis, 24 toxic epidermal necrolysis, 25 sarcoid-like reaction, 26 and photosensitivity. 27 Treatment discontinuation due to adverse events among different ALK inhibitors were as follow: 12% with crizotinib as in the PROFILE 1014 trial, 28 5% with ceritinib as in the ASCEND 4 trial, 29 11% with alectinib as in the ALEX trial, 30 12% with brigatinib as in the ALTA-1L trial, 10 and 7% with lorlatinib as in the CROWN trial.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with ALK inhibitors is usually well tolerated; however, there are common class adverse events such as nausea, vomiting, diarrhea, pneumonitis, and cardiac toxicity. 12 Some less common adverse events have been reported as well including rectal perforation, 13 cataract, macular edema or blindness, 14 , 15 osteitis, 16 ventricular fibrillation, 17 , 18 pulmonary arterial hypertension, 19 pancreatitis, 20 cholestasis, 21 alopecia, 22 proteinuria, 23 myasthenia gravis, 24 toxic epidermal necrolysis, 25 sarcoid-like reaction, 26 and photosensitivity. 27 …”
Section: Introductionmentioning
confidence: 99%